The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10661-010-1700-4
|View full text |Cite
|
Sign up to set email alerts
|

Eco-physiological performance of two invasive weed congeners (Ageratum conyzoides L. and Ageratum houstonianum Mill.) in the Indo-Gangetic plains of India

Abstract: Morphological (easily measureable) and physiological (hard to measure) traits of two closely related invasive alien congeners-Ageratum conyzoides L. and Ageratum houstonianum Mill. were studied with a perspective that which species will be potentially be more successful as an invader in the Indo-Gangetic plains of India. Leaf construction cost (LCC) is considered as a quantifiable measure of energy demand for biomass production and is related to energy use efficiency as it include component of both morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 46 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The photosynthetic rate of herbicide-treated A. conyzoides decreased due to the inhibition of protoporphyrinogen oxidase enzyme 38 , 39 as compared to the healthy weed having a photosynthetic rate of 13.2 μmol carbon dioxide (CO 2 ) m –2 s and leaf nitrogen content (2.3%) of 1.28 mg g –1 fresh weight chlorophyll. 48 Weed mortality percentage (80.33%) recorded in polymer–herbicide conjugate gel formulation dispersed @ 20 g a.i. ha –1 on A. conyzoides was significantly higher than that of weeds treated with herbicide-treated weeds (69.46%) @ 20 g a.i.…”
Section: Resultsmentioning
confidence: 99%
“…The photosynthetic rate of herbicide-treated A. conyzoides decreased due to the inhibition of protoporphyrinogen oxidase enzyme 38 , 39 as compared to the healthy weed having a photosynthetic rate of 13.2 μmol carbon dioxide (CO 2 ) m –2 s and leaf nitrogen content (2.3%) of 1.28 mg g –1 fresh weight chlorophyll. 48 Weed mortality percentage (80.33%) recorded in polymer–herbicide conjugate gel formulation dispersed @ 20 g a.i. ha –1 on A. conyzoides was significantly higher than that of weeds treated with herbicide-treated weeds (69.46%) @ 20 g a.i.…”
Section: Resultsmentioning
confidence: 99%
“…Both species of Ageratum are annual or perennial herbs that are native to the tropical Americas and invasive in Asia, Africa, and Oceania. Ecophysiological studies (Singh et al, 2011) and impact assessments (Shrestha et al, 2019) have revealed that A. houstonianum has higher invasiveness with more severe impacts than A. conyzoides . Adenostemma is phylogenetically close to the genus Ageratum as both of them belong to the tribe Eupatorieae (Fu et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The oven dried plant material was used to determine the ash content. Ash content was measured after combustion of the sample in a muffle furnace at 550°C for 6 h (Singh et al, 2011). C content was determined by using the loss on ignition method (Mcbrayer and Cromack, 1980) which is approximately 50% of ash-free weight (van Soest, 1963).…”
Section: Vegetation Sampling and Analysesmentioning
confidence: 99%